2020
DOI: 10.3390/ijerph17186801
|View full text |Cite
|
Sign up to set email alerts
|

Body Image Relates to Exercise-Induced Antinociception and Mood Changes in Young Adults: A Randomized Longitudinal Exercise Intervention

Abstract: Background: An important motivation for adolescents and young adults to engage in aerobic exercise (AE) is to improve fitness, body composition and physical appearance. These parameters have an impact on bodily perception as conceptualized by the ‘body image’ (BI) construct. AE is known to have positive effects on pain perception, mood, and body image (BI). However, no study has hitherto investigated their interrelationship within one study. Methods: Participants were randomly assigned to an intervention group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…Among the mechanisms that could explain the improvements observed in psychological well-being are better body image (physical efficacy) and antinociception, 43 the emotional and social support provided by the group session 37 and a greater release of serotonin 9 …”
Section: Discussionmentioning
confidence: 99%
“…Among the mechanisms that could explain the improvements observed in psychological well-being are better body image (physical efficacy) and antinociception, 43 the emotional and social support provided by the group session 37 and a greater release of serotonin 9 …”
Section: Discussionmentioning
confidence: 99%
“…This study is a sub-analysis within the “RUNSTUD” study ( Maurer et al, 2020 ). To test the influence of an extensive interval training over 6 months on brain structure and function, all subjects completed an extensive battery of neuropsychological, 3T and 7T MRI, and pain assessments before (timepoint at baseline: T0) and every 2 months (2, 4, and 6 months; timepoints T2, T4, and T6) after being randomized into an intervention group (IG) or control group (CG) ( Figure 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…Cassilhas’s study showed that moderate-intensity anaerobic exercise leads to a greater improvement in the mood [ 19 ]. Some studies have also shown no clear relationship between exercise type and changes in the mood [ 20 , 21 ]. These different findings have stimulated our research interest.…”
Section: Introductionmentioning
confidence: 99%